IMPLEMENTATION OF E-LEARNING WITH SIPADI POLMED-BASED FLIPPED CLASSROOM MODEL IN BASIC JAPANESE LANGUAGE COURSES - Annalisa Sonaria Hasibuan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
This study titled Flipped Classroom Implementation in Japanese Language Teaching in Business Administration Study Program aims to help students in understanding Japanese language courses as additional foreign languages that must be studied for two semesters. Flipped Classroom is one of the teaching methods where students get learning materials along with exercises and assignments (individuals or groups) in the form of videos and access them online through Sipadi, to be done outside the classroom to then be discussed during the course hours. Therefore, in class the teacher is reviewing materials, discussing assignments or exercises, and answering questions of students who still do not understand about the materials provided. While students at the time of the learning is expected to have gained an understanding of the material delivered. This method is tried to overcome the time constraints given for this course, which is only once a week for three hours of lectures. In addition, the condition of learning during the pandemic requires kbm to be done online, so that with this method students are not saturated, can be more active and also independent in accessing materials, learning can be carried out not limited by space and time. It is expected that with the implementation of this method, students' involvement in teaching and learning activities in the classroom increases and can easily understand the materials delivered.